Addition of salmeterol to existing treatment in patients with COPD: a 12 month study - Stockley, R A (BMJ Group, 2006)
BACKGROUND: This study investigated the addition of salmeterol to existing treatment for exacerbations in patients with poorly reversible chronic obstructive pulmonary disease (COPD). METHODS: 634 patients aged >40 years with a history of COPD exacerbations (including at least two in the previous year) and poor reversibility of airflow obstruction (⩽10% predicted forced expiratory volume in 1 second) received either salmeterol 50 μg or placebo twice daily from a Diskus inhaler for 12 months. The primary outcome was the number of moderate and severe exacerbations. RESULTS: The median rate of moderate or severe exacerbations in the intent‐to‐treat (ITT) population was lower in the salmeterol group (0.00, range 0.0–9.8, n = 316) than in the placebo group (0.93, range 0.0–13.0, n = 318), but the difference was not statistically significant (p = 0.27). The median rate of exacerbations in the per protocol population (>90% compliance) was also found to be lower in the salmeterol group (0.00, range 0.0–5.0, n = 206) than in the placebo group (0.93, range 0.0–5.6, n = 195) and did reach statistical significance (p = 0.007). For secondary end points, patients receiving salmeterol had significant improvement in lung hyperinflation measured by inspiratory capacity which was evident at 4 weeks and maintained over 12 months (p = 0.035), and a significant improvement in health status measured by the St George's Respiratory Questionnaire at 12 months (p = 0.002). CONCLUSION: Salmeterol has a positive effect on symptoms and health status of patients with COPD when added to usual treatment. Exacerbations are only reduced in patients who comply with treatment.